QUANTIFICATION OF THE NOVEL „THE NIGHT IN LISBON” BY E. M. REMARK AND ITS TRANSFER INTO UKRAINIAN LANGUAGE - Ліхнякевич, Ігор; Кульчицький, Ігор (Current Issues of Foreign Philology, 2021)
The idiostyle implies the system of meaningful and formal linguistic features inherent in the writings of a particular author, which makes the author's way unique in terms of verbalization embodied in these works. Idiolect is also a peculiar language of an individual. The idiostyle of the linguistic personality of the language professionals includes: a) the language of their works; b) the attitude towards language as a social, historical and cultural phenomenon; c) the usage of linguistic variability in certain communicative situations. It is equally important to take into account the general processes of literary language, their connection with the language of the day. The purpose of this work is to investigate the vocabulary of the novel “The Night in Lisbon” by E. M. Remark and its translation into Ukrainian by Arkadiy Plyuto and Mykola Dyatlenko. The research methodology is of a complex nature, which is to apply both general scientific methods as well as linguistic and proper translation methods. The main thing is a quantitative analysis, which ensures achievement of the aim. To conduct the research, the source text and its translation have been converted into an electronic form in the textual format Unicode utf 8. The texts received were technically edited. To introduce the marks into the text was the next step in our research. They indicate the boundaries of paragraphs and sentences. Moreover, the direct language of the characters in the novel was considered. Subsequently, using the AntConc program, the frequency lists of original and translated word forms have been obtained. The resulting word forms were arranged according to the vocabulary standards. As a result, for the original and translation, the total number of words (N), the number of word forms (Nf), the basic amount of words (L), and the number of words, which has occurred in the text only once (H) have been acquired. On their basis, the following coefficients have been calculated: the richness of the dictionary (index of diversity) – L / N; repeatability index – N / L; hapax legomena index – H / N; the index of exclusivity in the text – H / N and the index of concentration – the ratio of the number of words that are repeated 10 times or more to the number of words in the text – F10 / N. The research allowed to reveal the peculiarity of reproduction of the author’s idiolect in the source text and the degree of its preservation in the Ukrainian translation by quantitative parameterization of the source text and the target text using a parallel corpus.